Control management and causes of anger in teachers who work in primary school in elaziğ - Öztürk, Efraim; Boydak Özan, Mukadder (T.C. Milli Egitim Bakanligi, 2015)
It is normal that teachers feel anger in education atmosphere due to problems they faced like other people. That they show their anger positively and manage their anger effectively is important to increase quality of education. To research teachers opinions about anger and determine anger expression types and anger management styles, furthermore, to identify whether there is a diversity or not among these criterias according to gender have been intended. Research was carried out within mix model and as data collection tool, 50 item likert scale was applied. According to results reached, women teachers' opinions, which are regarding to reason and wording of anger, have turned out to be significantly higher. As far in the stage of management of anger, among the opinions according to gender significant differnce have not been founded. When anger and expressing of anger are regarded, it is seen that teachers generally live anger in dimension of school management and student,and they show their anger positively. It is emerged that teachers,which apply many strategies in anger management, act decisively about manage their anger.
Elaziğ i?li?ndeki i?lköğreti?m kurumlarinda çalişan öğretmenleri?n öfke nedenleri ve öfke kontrol yöneti?mleri
Keywords: Anger; Anger management; Teacher